Spherical non-precious metal propane dehydrogenation catalyst and preparation method and application thereof
By using a spherical non-noble metal propane dehydrogenation catalyst, which consists of alumina and SBA-16 mesoporous molecular sieve, and is prepared by ultrasonic assisted and vulcanized treatment, the existing catalyst cost and environmental pollution are solved, and efficient propane dehydrogenation and propylene selectivity are achieved.
Patent Information
- Application Number
- CN202210090040.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-01-25
AI Technical Summary
The existing propane dehydrogenation catalysts have problems such as high cost or easy to cause environmental pollution, and the catalyst performance such as selectivity and stability are insufficient.
A spherical non-noble metal propane dehydrogenation catalyst consisting of a composite support and metal and non-metal components supported on the support, which include alumina and SBA-16 mesoporous molecular sieve, was prepared by ultrasonic assisted and vulcanization treatment.
Good propane dehydrogenation activity, propylene selectivity and catalyst stability are achieved, while reducing the preparation cost of the catalyst and avoiding environmental pollution.
Smart Images

Figure CN116532147B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, and in particular to a spherical non-precious metal propane dehydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] Propylene is a very important organic chemical raw material, which can be used to produce chemical products such as polypropylene, acrolein, acrylic acid, glycerol, isopropanol, polyacrylonitrile, butanol and octanol. At present, propylene mainly comes from refinery by-products and steam cracking co-production. Recently, with the vigorous development of coal chemical industry, the realization of MTP process has effectively increased the source of propylene. Even so, the supply gap of propylene still cannot be made up. Under the above background, propane dehydrogenation to propylene has become one of the important ways to increase propylene production. Propane dehydrogenation technology is mainly divided into direct dehydrogenation and oxidative dehydrogenation, among which direct dehydrogenation technology has been industrialized in the 1990s. The industrially applied propane direct dehydrogenation catalysts are mainly Cr-based catalysts and Pt-based catalysts. The Catofin process developed by Lummus, the Linde process developed by Linde & BASF and the FBD process developed by Snamprogetti use Cr-based catalysts, and the Oleflex process developed by UOP and the Star process developed by Phillips use Pt-based catalysts. Cr-based catalysts are low in price but easy to deactivate, and heavy metal chromium can cause serious environmental pollution. Relatively speaking, Pt-based catalysts have higher activity, better selectivity and stability, but the precious metal platinum is expensive and the catalyst cost is high. Therefore, for various processes of propane dehydrogenation to propylene, the development of catalysts that do not use non-metallic components that cause serious environmental pollution, have higher dehydrogenation catalytic activity and better stability are the main technical issues that need to be solved urgently.
[0003] In order to improve the performance indicators of propane dehydrogenation catalysts, researchers have done a lot of work to improve Cr-based catalysts and Pt-based catalysts.
[0004] The reaction performance of Pt catalyst is improved by the method of oxide carrier modification (CN106607100A, CN106607099A), the catalyst activity is improved by improving the catalyst preparation method (CN103418376A, CN106944081A), the catalytic performance of Cr catalyst is improved by adding an auxiliary agent (CN104549220A), and the addition of Cr component is avoided by developing a multi-component catalyst formula (CN102451677B, CN104607168A). Although the prior art has improved the industrial application of Cr catalyst to a certain extent, there are still problems such as complex catalyst components, cumbersome preparation process, and catalyst performance to be improved. The Cr catalyst currently used in industry is prepared with alumina as a carrier. Although the alumina carrier is cheap, the pore size distribution is uneven and the specific surface area is also small, which is not conducive to the dispersion of active metal components on the carrier surface, nor is it conducive to the diffusion of raw materials and products during the reaction.
[0005] Therefore, developing a suitable carrier with excellent performance is an effective way to improve the performance of propane dehydrogenation catalysts. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of the existing propane dehydrogenation catalyst for propylene production, such as high cost or easy environmental pollution, and to provide a spherical non-precious metal propane dehydrogenation catalyst and its preparation method and application. The spherical non-precious metal propane dehydrogenation catalyst of the present invention can achieve good propane dehydrogenation activity, propylene selectivity and stability without using precious metals and seriously polluting metal components.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a spherical non-precious metal propane dehydrogenation catalyst, wherein the catalyst comprises a composite carrier and a metal component and a non-metal component supported on the composite carrier, the composite carrier comprises alumina and SBA-16 mesoporous molecular sieve, and the specific surface area of the composite carrier is 400-900m 2 / g, the pore volume is 0.4-1.2mL / g, the pore size distribution is a bimodal distribution, and the most probable pore sizes corresponding to the bimodal distribution are 4-7nm and 12-25nm, respectively.
[0008] The second aspect of the present invention provides a method for preparing a spherical non-precious metal propane dehydrogenation catalyst, wherein the preparation method comprises:
[0009] (Z1) contacting a solution containing a metal component precursor with a composite support under ultrasound-assisted conditions, removing the solvent, drying and calcining to obtain an initial catalyst; wherein the composite support comprises alumina and SBA-16 mesoporous molecular sieve;
[0010] (Z2) The initial catalyst is subjected to a sulfurization treatment using a sulfur-containing gas to obtain a spherical non-precious metal propane dehydrogenation catalyst.
[0011] The third aspect of the present invention provides a spherical non-precious metal propane dehydrogenation catalyst prepared by the above-mentioned preparation method.
[0012] A fourth aspect of the present invention provides an application of the aforementioned spherical non-precious metal propane dehydrogenation catalyst in the dehydrogenation of propane to propylene.
[0013] Through the above technical solution, the technical solution of the present invention has the following advantages:
[0014] (1) The spherical non-precious metal propane dehydrogenation catalyst of the present invention does not contain precious metals, and can effectively reduce the preparation cost of the propane dehydrogenation catalyst;
[0015] (2) The spherical non-precious metal propane dehydrogenation catalyst of the present invention does not contain chromium and is environmentally friendly;
[0016] (3) The spherical non-precious metal propane dehydrogenation catalyst of the present invention exhibits excellent catalytic performance when used for the propane dehydrogenation reaction to produce propylene, with high propane conversion rate, high propylene selectivity and good catalyst stability;
[0017] (4) The preparation method of the spherical non-precious metal propane dehydrogenation catalyst of the present invention has a simple process, easy-to-control conditions, and good product reproducibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a photograph of the spherical alumina-SBA-16 carrier A prepared in Example 1;
[0019] Figure 2 is a pore size distribution diagram of the spherical alumina-SBA-16 carrier A prepared in Example 1;
[0020] Figure 3 is the small angle XRD spectrum of the spherical alumina-SBA-16 carrier A prepared in Example 1;
[0021] Figure 4 It is the wide-angle XRD spectrum of the spherical alumina-SBA-16 carrier A prepared in Example 1. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] As mentioned above, the first aspect of the present invention provides a spherical non-precious metal propane dehydrogenation catalyst, wherein the catalyst comprises a composite carrier and a metal component and a non-metal component supported on the composite carrier, the composite carrier comprises alumina and SBA-16 mesoporous molecular sieve, and the specific surface area of the composite carrier is 400-900m 2 / g, the pore volume is 0.4-1.2mL / g, the pore size distribution is a bimodal distribution, and the most probable pore sizes corresponding to the bimodal distribution are 4-7nm and 12-25nm, respectively.
[0024] The inventors of the present invention found during the research on the preparation of propane dehydrogenation catalysts that: in the prior art, compared with Pt-based dehydrogenation catalysts, Cr-based catalysts have lower costs, but Cr-based catalysts have poor stability and serious pollution. Based on this, in order to maintain low catalyst costs and take environmental requirements into consideration, non-precious metal elements are used in the prior art to replace Cr to prepare dehydrogenation catalysts. The research on alternative catalysts has lasted for nearly twenty years, but the performance of alternative catalysts still cannot fully reach the level of Cr-based catalysts, mainly manifested in low selectivity, poor stability and other aspects. For non-precious metal catalysts, if the oxidized metal component is deeply reduced in the reducing atmosphere of the propane dehydrogenation reaction, it is easy to form a pure metal component, and the pure metal component has a very strong dehydrogenation performance, resulting in deep dehydrogenation or hydrogenolysis of propane, and the selectivity of propylene will be seriously reduced.
[0025] Further, the inventors of the present invention found in the study of the preparation of propane dehydrogenation catalysts that the prior art uses γ-alumina or silicon oxide as a carrier to load non-precious metal components to prepare propane dehydrogenation catalysts, which has the disadvantages of poor propylene selectivity and poor stability. Although commercially available alumina carriers or silicon oxide carriers are cheap, the pore size distribution is uneven and the specific surface area is small, which is not conducive to the dispersion of active metal components on the carrier surface, nor is it conducive to the diffusion of raw materials and products during the reaction. In comparison, SBA-16 all-silicon mesoporous molecular sieve materials have large specific surface area, large pore volume, and uniform pore size, which is more conducive to the diffusion of reactant molecules and product molecules in the reaction. However, the bulk density of SBA-16 all-silicon mesoporous molecular sieve materials is relatively small, and the volume is too large after being prepared into a catalyst, which will limit its industrial application. The inventors of the present invention found that by combining the structural advantages of alumina with SBA-16 all-silicon mesoporous molecular sieve materials, and preparing a spherical alumina-SBA-16 carrier by a specific molding method, a propane dehydrogenation catalyst with excellent performance can be obtained after loading non-precious metal active components.
[0026] Furthermore, the inventors of the present invention have found that if a non-precious metal catalyst is subjected to a sulfurization treatment so that the S element exists on the catalyst surface, the S element will combine with the active metal component to form a sulfide in the reducing atmosphere of the propane dehydrogenation reaction. The presence of non-precious metal sulfides can effectively prevent the metal component from being deeply reduced, thereby reducing the pure metal component on the catalyst surface and significantly inhibiting the occurrence of side reactions such as hydrogenolysis. The selectivity and stability of the dehydrogenation catalyst treated with sulfurization in the propane dehydrogenation reaction to produce propylene are significantly improved. For non-precious metal propane dehydrogenation catalysts, the S element content on their surface has a significant effect on the catalyst performance. If the S content is too low, the protective effect on the active metal component is limited, and some oxidized metal components will still be completely reduced to a pure metal state during the reaction; if the S content is too high, it will slow down the "oxidation-reduction" cycle rate of the active sites on the catalyst surface, thereby slowing down the reaction rate, which is manifested as a low catalyst activity.
[0027] According to the present invention, preferably, the specific surface area of the composite carrier is 450-800m 2 / g, pore volume is 0.5-1.0mL / g, pore size distribution is bimodal, and the most probable pore sizes corresponding to the bimodal distribution are 4.5-6.5nm and 14-20nm respectively; more preferably, the specific surface area of the composite carrier is 516-628m 2 / g, the pore volume is 0.6-0.8mL / g, the pore size distribution is bimodal, and the most probable pore sizes corresponding to the bimodal distribution are 5.2-6.3nm and 15-18nm respectively;
[0028] According to the present invention, based on the total weight of the composite carrier, the content of alumina is 55-75% by weight, and the content of SBA-16 mesoporous molecular sieve is 25-45% by weight; preferably, based on the total weight of the composite carrier, the content of alumina is 58.3-69.5% by weight, and the content of SBA-16 mesoporous molecular sieve is 30.5-41.7% by weight.
[0029] According to the present invention, the metal component element is selected from one or more of iron, nickel, zinc, tungsten, tin, manganese, molybdenum and copper; preferably, the metal component element is selected from one or more of iron, nickel, zinc, tungsten and tin; more preferably, the metal component element is selected from one or more of iron, nickel and zinc.
[0030] According to the present invention, the non-metal component is S element.
[0031] According to the present invention, based on the total weight of the catalyst, the content of the metal component is 3-30% by weight, the content of the non-metal component is 0.1-3% by weight, and the content of the composite carrier is 67-97% by weight; preferably, based on the total weight of the catalyst, the content of the metal component is 5-20% by weight, the content of the non-metal component is 0.2-1.5% by weight, and the content of the composite carrier is 79-95% by weight; more preferably, based on the total weight of the catalyst, the content of the metal component is 7.9-18.4% by weight, the content of the non-metal component is 0.5-1.2% by weight, and the content of the composite carrier is 80.4-91.6% by weight. In the present invention, the contents of the metal component, the non-metal component and the composite carrier (spherical alumina-SBA-16 carrier) are limited to the above range, which can simultaneously ensure that the active components of the catalyst are evenly dispersed and the pore structure is conducive to the diffusion of reactants and products.
[0032] According to the present invention, the preparation method of the composite carrier comprises:
[0033] (1) contacting and mixing an alumina precursor, an SBA-16 mesoporous molecular sieve, an acidic aqueous solution and an extrusion aid, and pelletizing the obtained mixture to obtain a spherical alumina-SBA-16 precursor;
[0034] (2) Drying and calcining the spherical alumina-SBA-16 precursor to obtain a composite carrier.
[0035] According to the present invention, the alumina precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide gel, aluminum sol, gibbsite and boehmite; preferably, pseudo-boehmite.
[0036] According to the present invention, the pseudo-boehmite can be obtained by commercial purchase or preparation. In the present invention, specifically, the pseudo-boehmite includes: German imported pseudo-boehmite powder of model SB (purchased from Beijing Asia Pacific Aohua Chemical Additives Co., Ltd., with a specific surface area of 241m 2 / g, pore volume 0.53cm 3 / g), pseudo-boehmite powder of model P-DF-09-LSi (produced by Shandong Aluminum Co., Ltd., with a specific surface area of 286m 2 / g, pore volume 1.08cm 3 / g) and macroporous pseudo-boehmite powder of model PB-0101 (produced by Zibo Hengqi Powder New Materials Co., Ltd., with a specific surface area of 327m 2 / g, pore volume 1.02cm 3 / g) in one or more.
[0037] According to the present invention, the SBA-16 mesoporous molecular sieve can be a homemade SBA-16 mesoporous molecular sieve. Preferably, the specific surface area of the SBA-16 mesoporous molecular sieve is 600-1000m 2 / g, pore volume is 0.4-1.0cm 3 / g, and an average pore size of 5-8nm; more preferably, the specific surface area of the SBA-16 mesoporous molecular sieve is 700-900m 2 / g, pore volume is 0.5-0.8cm 3 / g, and the average pore size is 5.5-7.5nm.
[0038] In a specific embodiment of the present invention, the preparation of the SBA-16 mesoporous molecular sieve comprises:
[0039] The template, acidic aqueous solution, n-butanol and chitosan are mixed evenly, and a silicon source is added; after contact reaction, the mixture is allowed to stand for crystallization; a solid product is obtained by separation; and the solid product is washed, dried and calcined to obtain an SBA-16 all-silica mesoporous molecular sieve.
[0040] In the method for preparing the SBA-16 mesoporous molecular sieve of the present invention, the template agent may be an amphiphilic triblock polymer, preferably F127 (polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, with the molecular formula EO106PO70EO106).
[0041] In the preparation method of SBA-16 mesoporous molecular sieve described in the present invention, the acidic aqueous solution can be an inorganic acid aqueous solution, preferably one or more of dilute hydrochloric acid or dilute nitric acid, more preferably dilute hydrochloric acid; the concentration of the acidic aqueous solution can be 0.2-10%, preferably 0.5-3%.
[0042] In the preparation method of the SBA-16 mesoporous molecular sieve described in the present invention, the silicon source can be an organic silicon-containing compound or an inorganic silicon-containing compound, preferably one or more of methyl orthosilicate, ethyl orthosilicate, isopropyl orthosilicate or silica sol, and more preferably ethyl orthosilicate.
[0043] In the method for preparing the SBA-16 mesoporous molecular sieve described in the present invention, the weight ratio of the template: acidic aqueous solution: n-butanol: chitosan: silicon source can be 1: (10-200): (0.2-10): (0.05-1.0): (1-8), preferably 1: (20-100): (0.5-3): (0.1-0.5): (2-4).
[0044] The preparation method of SBA-16 mesoporous molecular sieve in the present invention comprises the following mixing conditions: stirring rate of 50-300 r / min, temperature of 20-60°C, and time of 0.5-6h; preferably, stirring rate of 150-250 r / min, temperature of 20-40°C, and time of 0.5-3h.
[0045] In the method for preparing the SBA-16 mesoporous molecular sieve of the present invention, the contact reaction conditions may be a temperature of 50-150° C., preferably 80-120° C., and a time of 3-40 h, preferably 10-20 h.
[0046] In the preparation method of the SBA-16 mesoporous molecular sieve of the present invention, the conditions for the static crystallization can be a temperature of 50-150° C., preferably 80-120° C., and a time of 10-48 hours, preferably 16-30 hours.
[0047] The preparation method of the SBA-16 mesoporous molecular sieve described in the present invention has no special requirements for the solid-liquid two-phase separation process, and can be a separation method known in the art, including gravity filtration, pressure filtration, vacuum filtration or centrifugal filtration. Preferably, the separation process specifically includes: using a suction bottle, vacuuming the bottom side of the funnel or filtering using a centrifugal filter.
[0048] The preparation method of SBA-16 mesoporous molecular sieve described in the present invention has no special requirements for the method of washing the solid product. For example, the solid product can be washed with deionized water, the volume ratio of deionized water to the solid product can be 5-20, and the number of washing times can be 2-8 times.
[0049] In the method for preparing the SBA-16 mesoporous molecular sieve of the present invention, the drying conditions may be a temperature of 80-150° C., preferably 100-130° C., and a time of 2-30 h, preferably 5-20 h.
[0050] In the preparation method of the SBA-16 mesoporous molecular sieve of the present invention, the calcination conditions can be a temperature of 400-700° C., preferably 500-600° C., and a time of 2-24 h, preferably 4-12 h.
[0051] According to the present invention, the acidic aqueous solution can be an organic acid aqueous solution or an inorganic acid aqueous solution. Preferably, the acidic aqueous solution is selected from one or more of a formic acid aqueous solution, an acetic acid aqueous solution, a citric acid aqueous solution, a nitric acid aqueous solution and a hydrochloric acid aqueous solution. More preferably, the acidic aqueous solution is a nitric acid aqueous solution or a citric acid aqueous solution. In the present invention, the mass concentration of the acidic aqueous solution is 1-20%, preferably 2-10%.
[0052] According to the present invention, the extrusion aid is selected from one or more of sesbania powder, polyethylene glycol, polyvinyl alcohol, polyacrylamide and cellulose; preferably, the extrusion aid is sesbania powder.
[0053] According to the present invention, the weight ratio of the alumina precursor, the SBA-16 mesoporous molecular sieve, the extrusion aid and the acidic aqueous solution is 1: (0.2-1): (0.02-0.5): (0.2-5); preferably, the weight ratio of the alumina precursor, the SBA-16 mesoporous molecular sieve, the extrusion aid and the acidic aqueous solution is 1: (0.3-0.5): (0.07-0.12): (0.6-0.8).
[0054] According to the present invention, in step (1), the alumina precursor, the SBA-16 mesoporous molecular sieve, the acidic aqueous solution and the extrusion aid are contacted and mixed, and the mixing conditions include: a stirring rate of 50-300 r / min, a temperature of 20-60°C, and a time of 0.5-6h; preferably, the stirring rate is 150-250 r / min, the temperature is 20-40°C, and the time is 0.5-1h.
[0055] According to the present invention, in step (2), the drying conditions include: temperature of 70-150° C., time of 3-24 h; preferably, temperature of 100-130° C., time of 6-12 h.
[0056] According to the present invention, in step (2), the calcination conditions include: temperature of 400-700° C., time of 2-30 h; preferably, temperature of 550-700° C., time of 12-15 h.
[0057] According to the present invention, in step (1), the method for making micro-pellets comprises:
[0058] (1-1) extruding the mixture into long strips, and then cutting and extruding into raw material balls;
[0059] (1-2) shaping the raw material ball to obtain a standard round ball;
[0060] (1-3) Screening the standard spheres to obtain spherical precursors.
[0061] According to the present invention, in step (1-1), the alumina precursor, the SBA-16 mesoporous molecular sieve, the acidic aqueous solution and the extrusion aid are uniformly mixed, and the obtained mixture is transferred to a micro-ball making machine to extrude long strips with a circular cross-section, and then cut and extruded into raw material balls; wherein the conditions for extruding into strips include: the extrusion speed is 0.5-5m / min, and the circular cross-sectional diameter of the long strip is 1.5-5.0mm; the cutting conditions include: the cutting speed is 100-3500 particles / minute.
[0062] According to the present invention, in step (1-2), the raw material ball is placed in a micro-pellet shaping machine for shaping into a standard spherical shape; wherein the shaping treatment conditions include: a rounding time of 0.5-10 minutes / time, a rounding number of times of 1-5 times, and a sample chamber rotation speed of 50-1400r / min.
[0063] According to the present invention, in step (1-3), the standard spheres are placed in a pellet screening machine to screen out spherical precursors of suitable sizes.
[0064] The second aspect of the present invention provides a method for preparing a spherical non-precious metal propane dehydrogenation catalyst, wherein the preparation method comprises:
[0065] (Z1) contacting a solution containing a metal component precursor with a composite support under ultrasound-assisted conditions, removing the solvent, drying and calcining to obtain an initial catalyst; wherein the composite support comprises alumina and SBA-16 mesoporous molecular sieve;
[0066] (Z2) The initial catalyst is subjected to a sulfurization treatment using a sulfur-containing gas to obtain a spherical non-precious metal propane dehydrogenation catalyst.
[0067] The inventors of the present invention also found that the introduction of an ultrasonic-assisted method in the preparation process of the spherical non-precious metal propane dehydrogenation catalyst can promote better dispersion of the active components on the surface of the spherical alumina-SBA-16 carrier, thereby obtaining a propane dehydrogenation catalyst with better catalytic activity.
[0068] According to the present invention, the ultrasonic assisted conditions include: temperature of 10-100°C, time of 10-180min, and power of 100-300W; preferably, the ultrasonic assisted conditions include: temperature of 20-80°C, time of 30-120min, and power of 150-250W.
[0069] According to the present invention, the solution containing the metal component precursor is an aqueous solution or an ethanol solution containing the metal component precursor; preferably, the mass concentration of the solution containing the metal component precursor is 0.5-10%.
[0070] According to the present invention, the metal component precursor is selected from one or more of nitrates, sulfites or metal chlorides containing iron, nickel, zinc, tungsten, tin, manganese, molybdenum and copper.
[0071] According to the present invention, in step (Z1), the contact reaction conditions include: temperature of 20-100°C, preferably 40-80°C; time of 0.5-10h, preferably 2-8h.
[0072] According to the present invention, the method for removing the solvent is not particularly limited and may be a method known in the art, such as: removing the solvent by evaporating it using a rotary evaporator, or removing the solvent by heating and stirring.
[0073] According to the present invention, the drying conditions are not particularly limited and may be conventional conditions in the art. Preferably, the drying conditions include: a temperature of 60-150° C., preferably 80-130° C.; and a time of 1-20 hours, preferably 3-15 hours.
[0074] According to the present invention, the calcination conditions include: a temperature of 400-700° C., preferably 500-650° C.; and a calcination time of 2-15 h, preferably 3-10 h.
[0075] According to the present invention, the sulfur-containing gas is nitrogen, helium or argon containing hydrogen sulfide; the volume content of hydrogen sulfide in the sulfur-containing gas is 0.1-5% by volume, preferably 0.3-2% by volume.
[0076] According to the present invention, in step (Z2), the sulfurization treatment conditions include: temperature of 400-700°C, time of 1-15h; preferably, the treatment conditions include: temperature of 450-650°C, time of 2-8h.
[0077] The third aspect of the present invention provides a spherical non-precious metal propane dehydrogenation catalyst prepared by the above-mentioned preparation method.
[0078] A fourth aspect of the present invention provides an application of the aforementioned spherical non-precious metal propane dehydrogenation catalyst in the dehydrogenation of propane to propylene.
[0079] According to the present invention, the reaction comprises: contacting the reaction raw material propane with the spherical non-precious metal propane dehydrogenation catalyst for reaction.
[0080] According to the present invention, the contact conditions include: the contact temperature can be 550-650°C, the feed gas partial pressure is 0.02-0.5MPa, the mass space velocity of propane is 1.0-10.0h -1 .
[0081] In the following examples and comparative examples:
[0082] The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, USA. The samples were vacuum degassed at 350°C for 4 h before measurement. The specific surface area of the samples was calculated using the BET method, and the pore volume was calculated using the BJH model.
[0083] The elemental analysis experiment of the samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX Company in the United States;
[0084] The ultrasonic generator is a KQ-300GTDV high-frequency constant temperature CNC ultrasonic cleaner produced by Kunshan Ultrasonic Instrument Co., Ltd., with an ultrasonic frequency of 80kHz and an operating voltage of 220V;
[0085] The rotary evaporator was manufactured by IKA, Germany, model RV10 digital;
[0086] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.
[0087] The muffle furnace is produced by CARBOLITE, model CWF1100.
[0088] The kneading machine is a FN-NH2 kneading machine produced by Tianshui Huayuan Pharmaceutical Equipment Technology Co., Ltd.; the micro-ball making machine is a HWJ-100 micro-ball making machine produced by Tianshui Huayuan Pharmaceutical Equipment Technology Co., Ltd.; the pellet shaping machine is a FN-XZXJ pellet shaping machine produced by Tianshui Huayuan Pharmaceutical Equipment Technology Co., Ltd.; the pellet screening machine is a SWP-1200 pellet screening machine produced by Tianshui Huayuan Pharmaceutical Equipment Technology Co., Ltd.
[0089] F127 was purchased from Acros Reagent Co., Ltd. Other reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd., and the reagent purity was analytical grade.
[0090] The propane conversion rate is calculated as follows:
[0091] Propane conversion rate = amount of propane consumed in the reaction / initial amount of propane × 100%;
[0092] The propylene selectivity is calculated as follows:
[0093] Propylene selectivity = amount of propane consumed to produce propylene / total propane consumption × 100%.
[0094] Example 1
[0095] This example is intended to illustrate the spherical non-precious metal propane dehydrogenation catalyst prepared by the present invention.
[0096] (1) Preparation of spherical alumina-SBA-16 carrier
[0097] 1) Preparation of SBA-16 mesoporous molecular sieve
[0098] In a 1000ml round-bottom flask, add 10g polyether F127, 20g concentrated hydrochloric acid and 500mL deionized water, mix and stir for 30min; continue to add 15g n-butanol and 2g chitosan to the flask, stir for 1h; slowly add 25g ethyl orthosilicate, heat to 100℃, stir and crystallize for 16h, and then stand at 100℃ for crystallization for 24h. After the crystallization is completed, filter to obtain a white solid product, wash it with deionized water 8 times, dry it in air at 120℃ for 10 hours, and then calcine it at 550℃ for 8 hours to obtain SBA-16 mesoporous molecular sieve.
[0099] The specific surface area of SBA-16 mesoporous molecular sieve is 794m 2 / g, pore volume 0.65cm 3 / g, and the average pore size is 6.5nm.
[0100] 2) Preparation of spherical alumina-SBA-16 carrier
[0101] Mix 120g of P-DF-09-LSi pseudo-boehmite powder, 60g of SBA-16 mesoporous molecular sieve, 85g of 5% dilute nitric acid and 10g of sesbania powder, transfer to a kneader and stir to mix evenly. The kneading temperature is 35°C, the main shaft speed of the kneader is 150r / min, and the kneading time is 1h. Put the mixed raw materials into the hopper of a micro-ball making machine, select an extrusion die with an aperture of 1.8mm, adjust the extrusion speed to 2m / min, and the cutting speed to 1200 grains / min, extrude the raw materials into strips and extrude and cut into round small particles. Put the above-mentioned round small particles into a micro-pellet shaping machine for shaping, and the shaping conditions are as follows: the rounding time is 3min / time, the rounding number is 3 times, and the sample chamber speed is 300r / min. Put the standard spherical raw material balls obtained after shaping into a micro-pellet screening machine to screen out spherical precursors with a size of 1.7mm. The spherical precursor was dried at 110°C for 8 hours and then calcined at 600°C for 15 hours to obtain a spherical alumina-SBA-16 carrier A.
[0102] The spherical alumina-SBA-16 carrier A was characterized and its structural parameters are listed in Table 1.
[0103] Figure 1 is a photograph of spherical alumina-SBA-16 support A. Figure 1 It can be seen that the carrier has the appearance of a white sphere with good sphericity, smooth spherical surface and uniform particle size.
[0104] Figure 2 This is the pore size distribution diagram of spherical alumina-SBA-16 carrier A. The pore size of this sample is bimodal, with the first most probable pore size of 5.8 nm, mainly contributed by SBA-16 mesoporous molecular sieve; the second most probable pore size is 16.5 nm, mainly contributed by alumina.
[0105] Figure 3 is the low-angle XRD spectrum of the spherical alumina-SBA-16 carrier A prepared in Example 1; Figure 3 It can be seen that the sample has a strong diffraction peak at 2θ=0.78°, which belongs to the characteristic diffraction peak of the (110) crystal plane, and a weaker diffraction peak at 2θ=1.2°, which belongs to the characteristic diffraction peak of the (200) crystal plane. This shows that the SBA-16 molecular sieve in the spherical alumina-SBA-16 carrier A has a good Im3m-type body-centered cubic mesoporous structure. After mixed molding and calcination with the alumina precursor, the diffraction peak corresponding to the mesoporous structure is still obvious, indicating that the molding process has not changed the Im3m-type body-centered cubic mesoporous structure of the SBA-16 molecular sieve, and the orderliness of the pore space structure is still very high.
[0106] Figure 4 It is the wide-angle XRD spectrum of the spherical alumina-SBA-16 carrier A prepared in Example 1; the XRD wide-angle diffraction pattern of the spherical alumina-SBA-16 carrier A is exactly the same as the wide-angle diffraction pattern of alumina, because the structure of the SBA-16 mesoporous molecular sieve has no diffraction signal in the wide-angle part. The x-ray diffraction angles are mainly: 2θ=37.1°, 39.3°, 46.1°, 60.7° and 66.6°. These five diffraction signals are consistent with the γ-Al2O3 diffraction spectrum, indicating that after the spherical alumina-SBA-16 carrier A is calcined at 600°C, the pseudo-boehmite model P-DF-09-LSi presents a typical γ-Al2O3 crystal phase after dehydration. In addition, it should be noted that the XRD signal of the spherical alumina-SBA-16 carrier A cannot be displayed in one figure, nor can it be detected by the same characterization method. Therefore, the XRD patterns provided in the present invention are two, one at a wide angle and the other at a small angle.
[0107] (2) Preparation of spherical non-precious metal propane dehydrogenation catalyst
[0108] 10.8g of ferric nitrate nine hydrate was dissolved in 100g of deionized water, mixed with 10g of spherical alumina-SBA-16 carrier A, stirred and reacted for 60min at 50°C under the assistance of ultrasonic wave with power of 200W. After the reaction, the water in the system was evaporated by rotary evaporator to obtain a solid product. The solid product was placed in a drying oven at a temperature of 110°C and dried for 6 hours. Then it was calcined in a muffle furnace at a temperature of 550°C for 5 hours to obtain the initial catalyst A.
[0109] 10 g of the initial catalyst A was treated at 550° C. for 3 hours in a nitrogen gas flow with a H 2 S content of 1.5% to obtain a spherical non-precious metal propane dehydrogenation catalyst A.
[0110] The proportions of the components of the spherical non-precious metal propane dehydrogenation catalyst A are as follows: 13.6% by weight of iron element (calculated as metallic iron content), 0.8% by weight of sulfur element, and the rest being carrier.
[0111] The composition and structural parameters of Catalyst A are listed in Table 2.
[0112] (3) Catalyst performance evaluation in propane dehydrogenation to propylene
[0113] The reaction performance of the catalyst was evaluated in a fixed bed reactor. 5.0 g of catalyst A was loaded into a fixed bed quartz reactor, the reaction temperature was controlled to be 600 °C, the reaction pressure was 0.1 MPa, the molar ratio of propane to helium was 1:1, and the propane mass space velocity was 5.0 h -1 The reaction time was 6 h. The reaction products separated by the Al2O3-S molecular sieve column were directly fed into an Agilent 7890A gas chromatograph equipped with a hydrogen flame detector (FID) for online analysis. The reaction evaluation results are listed in Table 3.
[0114] Example 2-3
[0115] This example is intended to illustrate the spherical non-precious metal propane dehydrogenation catalyst prepared by the present invention.
[0116] Spherical non-precious metal propane dehydrogenation catalysts B and C were prepared in the same manner as in Example 1, wherein the SBA-16 mesoporous molecular sieve was prepared in the same manner as in step (1) of Example 1, except that:
[0117] By changing the parameters in the preparation process of spherical alumina-SBA-16 carrier in step (1) of Example 1, and carrying out Examples 2-3, spherical alumina-SBA-16 carriers B and C were obtained respectively. The structural parameters of spherical alumina-SBA-16 carriers B and C are listed in Table 1.
[0118] By changing the parameters in the catalyst preparation process in step (2) of Example 1, Examples 2-3 were carried out to obtain catalysts B and C, respectively. The preparation conditions, composition and structural parameters of catalysts B and C are listed in Table 2.
[0119] The propane dehydrogenation to propylene reaction performance test of catalysts B and C was carried out according to the method of step (3) in Example 1. The reaction results are shown in Table 3.
[0120] Embodiment 4-7
[0121] This example is intended to illustrate the spherical non-precious metal propane dehydrogenation catalyst prepared by the present invention.
[0122] Spherical alumina-SBA-16 carrier A was prepared according to the method in step (1) of Example 1, and various parameters in the catalyst preparation process in step (2) of Example 1 were changed to carry out Examples 4-7 to obtain catalysts D, E, F and G, respectively. The preparation conditions, composition and structural parameters of catalysts D, E, F and G are listed in Table 2.
[0123] The propane dehydrogenation to propylene reaction performance test of catalysts D, E, F and G was carried out according to the method of step (3) in Example 1. The reaction results are shown in Table 3.
[0124] Comparative Example 1
[0125] This comparative example is to illustrate that the carriers are different.
[0126] Step (1) in Example 1 was omitted, and catalyst D1 was prepared according to the method of step (2) in Example 1, except that "alumina" was used instead of "spherical alumina-SBA-16 carrier A" as the catalyst carrier; wherein the specific surface area of commercially available alumina was 224 m 2 / g, the pore volume is 0.69ml / g, the average particle diameter is 1.5mm, and the particle crushing strength is 12.6N.
[0127] Based on the total weight of the catalyst D1, the content of the metal element iron was 13.6% by weight, the content of S was 0.8% by weight, and the rest was carrier alumina.
[0128] The propane dehydrogenation to propylene reaction performance test of catalyst D1 was carried out according to the method of step (3) in Example 1. The reaction results are shown in Table 3.
[0129] Comparative Example 2
[0130] This comparative example is to illustrate that the preparation conditions are different and the catalyst components are different.
[0131] Spherical alumina-SBA-16 carrier A was prepared according to the method of step (1) in Example 1. Catalyst D2 was prepared according to the method of step (2) in Example 1, and the catalyst preparation conditions were adjusted, specifically:
[0132] 1.8 g of ferric nitrate nine hydrate was dissolved in 100 g of deionized water, mixed with 10 g of spherical alumina-SBA-16 carrier A, and stirred for 60 min at 50°C under the assistance of ultrasonic wave with a power of 200 W. After the reaction, the water in the system was evaporated by rotary evaporator to obtain a solid product. The solid product was placed in a drying oven at a temperature of 110°C and dried for 6 hours. Then it was calcined in a muffle furnace at a temperature of 550°C for 5 hours to obtain the initial catalyst D2.
[0133] 10 g of the initial catalyst D2 was treated at 600° C. for 15 hours in a nitrogen gas flow with a H2S content of 1.5% to obtain a spherical non-precious metal propane dehydrogenation catalyst D2.
[0134] Based on the total weight of the catalyst D2, the content of the metal element iron is 2.3% by weight, the content of S is 3.2% by weight, and the rest is the carrier.
[0135] The propane dehydrogenation to propylene reaction performance test of catalyst D2 was carried out according to the method of step (3) in Example 1. The reaction results are shown in Table 3.
[0136] Comparative Example 3
[0137] This comparative example is intended to illustrate the non-sulfurization process.
[0138] Spherical alumina-SBA-16 carrier A was prepared according to the method of step (1) in Example 1. Catalyst D3 was prepared according to the method of step (2) in Example 1, and the sulfidation process of the initial catalyst was omitted, so that the content of the metal element iron was 13.6% by weight based on the total weight of catalyst D3, and the rest was carrier.
[0139] The propane dehydrogenation to propylene reaction performance test of catalyst D3 was carried out according to the method of step (3) in Example 1. The reaction results are shown in Table 3.
[0140] Comparative Example 4
[0141] This comparative example is to illustrate that the carriers are different.
[0142] A spherical propane dehydrogenation catalyst was prepared in the same manner as in Example 1, except that step (1) in Example 1 was omitted and catalyst D4 was prepared in the same manner as in Example 1 (2), except that "SBA-16 mesoporous molecular sieve" was used instead of "spherical alumina-SBA-16 carrier A" as the catalyst carrier; wherein the specific surface area of the SBA-16 mesoporous molecular sieve was 794 m 2 / g, pore volume 0.65cm 3 / g, and the average pore size is 6.5nm.
[0143] Based on the total weight of the catalyst D4, 13.6 wt% of the iron element (calculated as metallic iron content), 0.8 wt% of the sulfur element, and the rest are carriers.
[0144] The reaction performance of catalyst D4 was evaluated according to the method of step (3) in Example 1. The reaction results are shown in Table 2.
[0145] Comparative Example 5
[0146] This comparative example is to illustrate the different contents of components in the composite carrier.
[0147] A spherical propane dehydrogenation catalyst was prepared in the same manner as in Example 1, except that in (1) the preparation of the spherical alumina-SBA-16 carrier, "120 g of pseudo-boehmite powder of model P-DF-09-LSi, 60 g of SBA-16 mesoporous molecular sieve, 85 g of 5% dilute nitric acid and 10 g of sesbania powder were mixed" was replaced with "45 g of pseudo-boehmite powder of model P-DF-09-LSi, 70 g of SBA-16 mesoporous molecular sieve, 60 g of 5% dilute nitric acid and 7 g of sesbania powder were mixed"; a spherical alumina-SBA-16 carrier D5 was prepared.
[0148] Results Based on the total weight of the spherical alumina-SBA-16 carrier D5, the iron content (calculated as metallic iron content) was 31.0% by weight, and the SBA-16 mesoporous molecular sieve content was 69.0% by weight.
[0149] Among them, the specific surface area of spherical alumina-SBA-16 carrier D5 is 651m 2 / g, and the pore volume is 0.7ml / g.
[0150] Catalyst D5 was prepared according to the method of step (2) in Example 1.
[0151] Based on the total weight of the catalyst D5, 13.6 wt% of the iron element (calculated as metallic iron content), 0.8 wt% of the sulfur element, and the rest are carriers.
[0152] The performance test of catalyst D5 for dehydrogenation of propylene to propylene was carried out according to the method of step (3) in Example 1. The reaction results are shown in Table 2.
[0153] Table 1
[0154]
[0155]
[0156] Table 2
[0157]
[0158] Table 2 (continued)
[0159]
[0160] Table 3
[0161]
[0162]
[0163] It can be seen from Table 3 that:
[0164] (1) The spherical non-precious metal propane dehydrogenation catalyst prepared by the method of the present invention has excellent performance when used in the propane dehydrogenation reaction to produce propylene.
[0165] (2) By comparing the experimental results of Example 1 and Comparative Example 1, it can be found that the performance of Catalyst A prepared using spherical alumina-SBA-16 carrier is significantly better than that of Catalyst D1 prepared using alumina as a carrier, and the propane conversion rate, propylene selectivity, and catalyst stability are greatly improved. The above results show that the spherical alumina-SBA-16 carrier is more conducive to the propane dehydrogenation to propylene reaction.
[0166] (3) By comparing the experimental results of Example 1 and Comparative Example 2, it can be found that the performance (propane conversion rate, propylene selectivity and catalyst stability) of the D2 catalyst whose component contents are not within the scope of the claims is poor, indicating that only when the active components and additives loaded on the carrier are within a certain content range can a propane dehydrogenation catalyst with excellent performance be obtained.
[0167] (4) By comparing the experimental results of Example 1 and Comparative Example 3, it can be found that the performance of the sulfurized catalyst A is significantly better than that of the sulfur-free catalyst D3, and the propane conversion rate and propylene selectivity are significantly improved; the performance of the catalyst A is almost unchanged during the 6-hour reaction, while the propane conversion rate and propylene selectivity of the D3 catalyst are significantly reduced. The above results show that the presence of S element on the catalyst surface can effectively improve the dehydrogenation activity of the catalyst, the selectivity of the target olefin and the stability of the catalyst.
[0168] (5) By comparing the experimental results of Example 1 and Comparative Example 4, it can be found that when SBA-16 mesoporous molecular sieve is used to replace spherical alumina-SBA-16 carrier A as a catalyst carrier, no matter how the catalyst performance is, the catalyst cannot be industrially applied. This is because SBA-16 mesoporous molecular sieve is a powder and cannot be formed without a binder. The catalysts used in industrial applications are all pre-formed samples.
[0169] (6) By comparing the experimental results of Example 1 and Comparative Example 5, it can be found that the ratio of alumina to SBA-16 mesoporous molecular sieve in the spherical alumina-SBA-16 carrier D5 is not within the range specified by the present invention, the shape of the prepared shaped carrier is not regular enough, and the internal components are not evenly dispersed. After being loaded with active components as a carrier, the uniform dispersion of the active components is also affected. Therefore, compared with Catalyst A, the performance of Catalyst D5 is poor.
[0170] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A spherical non-precious metal propane dehydrogenation catalyst, characterized in that: The catalyst comprises a composite carrier and a metal component and a non-metal component supported on the composite carrier, wherein the metal component element is selected from one or more of iron, nickel, zinc, tungsten, tin, manganese, molybdenum and copper, and the non-metal component is S element; and based on the total weight of the catalyst, the content of the metal component is 3-30% by weight, the content of the non-metal component is 0.1-3% by weight, and the content of the composite carrier is 67-95% by weight; the composite carrier comprises alumina and SBA-16 mesoporous molecular sieve, and the specific surface area of the composite carrier is 400-900m 2 / g, the pore volume is 0.4-1.2mL / g, the pore size distribution is a bimodal distribution, and the most probable pore sizes corresponding to the bimodal distribution are 4-7nm and 12-25nm, respectively.
2. The catalyst according to claim 1, wherein The specific surface area of the composite carrier is 450-800m 2 / g, the pore volume is 0.5-1.0mL / g, the pore size distribution is bimodal, and the most probable pore sizes corresponding to the bimodal distribution are 4.5-6.5nm and 14-20nm respectively; And / or, based on the total weight of the composite carrier, the content of the alumina is 55-75% by weight, and the content of the SBA-16 mesoporous molecular sieve is 25-45% by weight.
3. The catalyst according to claim 2, wherein The specific surface area of the composite carrier is 516-628m 2 / g, the pore volume is 0.6-0.8mL / g, the pore size distribution is bimodal, and the most probable pore sizes corresponding to the bimodal distribution are 5.2-6.3nm and 15-18nm respectively; And / or, based on the total weight of the composite carrier, the content of the alumina is 58.3-69.5% by weight, and the content of the SBA-16 mesoporous molecular sieve is 30.5-41.7% by weight.
4. The catalyst according to claim 1, wherein Based on the total weight of the catalyst, the content of the metal component is 5-20% by weight, the content of the non-metal component is 0.2-1.5% by weight, and the content of the composite carrier is 79-91.6% by weight.
5. The catalyst according to claim 4, wherein Based on the total weight of the catalyst, the content of the metal component is 7.9-18.4% by weight, the content of the non-metal component is 0.5-1.2% by weight, and the content of the composite carrier is 80.4-91.6% by weight.
6. The catalyst according to any one of claims 1 to 5, wherein The preparation method of the composite carrier comprises: (1) contacting and mixing an alumina precursor, an SBA-16 mesoporous molecular sieve, an acidic aqueous solution and an extrusion aid, and pelletizing the obtained mixture to obtain a spherical alumina-SBA-16 precursor; (2) Drying and calcining the spherical alumina-SBA-16 precursor to obtain a composite carrier.
7. The catalyst according to claim 6, wherein The alumina precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide gel, aluminum sol, gibbsite and boehmite; And / or, the weight ratio of the alumina precursor, the SBA-16 mesoporous molecular sieve, the extrusion aid and the acidic aqueous solution is 1: (0.2-1): (0.02-0.5): (0.2-5).
8. The catalyst according to claim 6, wherein The method for making micro-pellets comprises: (1-1) extruding the mixture into long strips, and then cutting and extruding into raw material balls; (1-2) shaping the raw material balls to obtain standard round balls; (1-3) The standard spheres are screened to obtain spherical precursors.
9. The catalyst according to claim 8, wherein The conditions for extruding into long strips include: the extrusion speed is 0.5-5m / min, and the diameter of the circular cross section of the long strip is 1.5-5.0mm; And / or, the cutting conditions include: a cutting speed of 100-3500 grains / minute; And / or, the conditions of the shaping treatment include: the rounding time is 0.5-10 minutes / time, the rounding times are 1-5 times, and the sample chamber rotation speed is 50-1400r / min.
10. A method for preparing the spherical non-precious metal propane dehydrogenation catalyst according to any one of claims 1 to 9, characterized in that: The preparation method comprises: (Z1) Under ultrasonic-assisted conditions, a solution containing a metal component precursor is contacted with a composite support for reaction, and an initial catalyst is obtained by removing the solvent, drying and calcining; wherein the composite support comprises alumina and SBA-16 mesoporous molecular sieve; (Z2) The initial catalyst is subjected to a sulfurization treatment using a sulfur-containing gas to obtain a spherical non-precious metal propane dehydrogenation catalyst.
11. The preparation method according to claim 10, wherein: The ultrasonic-assisted conditions include: temperature of 10-100° C., time of 10-180 min, and power of 100-300 W.
12. The preparation method according to claim 11, wherein The ultrasonic-assisted conditions include: temperature of 20-80° C., time of 30-120 min, and power of 150-250 W.
13. The preparation method according to claim 10, wherein: The solution containing the metal component precursor is an aqueous solution or an ethanol solution containing the metal component precursor.
14. The preparation method according to claim 10 or 13, wherein: The metal component precursor is selected from one or more of nitrates, sulfites or metal chlorides containing iron, nickel, zinc, tungsten, tin, manganese, molybdenum and copper.
15. The preparation method according to claim 10, wherein: The sulfur-containing gas is nitrogen, helium or argon containing hydrogen sulfide; and / or, the volume content of the hydrogen sulfide in the sulfur-containing gas is 0.1-5% by volume; And / or, in step (Z1), the calcination conditions include: temperature of 400-700°C and time of 2-15h; And / or, in step (Z1), the contact reaction conditions include: temperature of 20-100°C, time of 0.5-10h; And / or, in step (Z2), the sulfurization treatment conditions include: temperature of 400-700° C. and time of 1-15 h.
16. The preparation method according to claim 15, wherein: The volume content of hydrogen sulfide in the sulfur-containing gas is 0.3-2% by volume; And / or, in step (Z1), the calcination conditions include: temperature of 500-650°C; time of 3-10h; And / or, in step (Z2), the sulfurization treatment conditions include: temperature of 450-650° C. and time of 2-8 h.
17. A spherical non-precious metal propane dehydrogenation catalyst prepared by the preparation method according to any one of claims 10 to 16.
18. Use of the spherical non-precious metal propane dehydrogenation catalyst according to any one of claims 1 to 9 in the dehydrogenation of propane to produce propylene.
Citation Information
Patent Citations
Catalyst for alkane dehydrogenation and device
CN102451677B
Anti-sintering catalyst for preparing low-carbon olefin by low-carbon alkane dehydrogenation and preparation method thereof
CN103418376A
Catalyst for dehydrogenating light alkane
CN104549220A
Catalyst used for alkane catalytic dehydrogenation and preparation method thereof
CN104607168A
Catalyst for preparing low-carbon olefin by dehydrogenizing low-carbon alkane and preparation method of catalyst
CN106607099A